How to Implement the Talent Training of "Integration of Sports and Medicine" in Colleges and Universities under the New Development Concept - Xu Zhang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
In light of contemporary developments, the convergence of sports and medicine has emerged as a novel proposition and healthcare concept in the modern era. The realization and execution of this concept necessitate active involvement from diverse sectors of society, with a particular emphasis on the indispensable role of physical education programs within colleges and universities. Against this backdrop, the present study was devised to assess the factors conducive to enhancing the integration of sports and medicine through talent development. Consequently, a cross-sectional research design was employed, and quantitative data were gathered from Chinese students via a simple random sampling technique. The collected data were subsequently subjected to examination using Partial Least Squares (PLS) analysis. The findings underscore the support for all stipulated hypotheses in the study. These results hold significant implications for the transformation and advancement of physical education curricula within higher education institutions.